Engaging in transnational ways of teaching and building a community of practice: Preservice teachers’ experiences in an online after‐school program - Kwon, Jungmin (Foreign language annals, 2025)
Employing the concepts of transnational funds of knowledge and community practice, this ethnographic case study examines the experiences of preservice world language teachers in a year‐long teaching methods course. It focuses on an online after‐school program where preservice teachers taught languages and cultures to children from linguistically and culturally diverse backgrounds. The findings illustrate how a teacher candidate from a multilingual and immigrant background drew on her transnational lived experiences and encouraged students to think beyond the boundaries of languages, cultures, and countries. Findings also show how preservice teachers in the program learned from fellow teachers’ practices and built a shared repertoire of resources to engage in transnational ways of teaching language and culture. This study underscores the importance of providing clinical opportunities where preservice teachers can put theory into practice, incorporate transnational funds of knowledge that learners possess, and challenge linguistic, cultural, and geographic boundaries.